Pengaruh Pemberian Motivasi Belajar Oleh Guru PAK Terhadap Hasil Belajar Siswa Kelas Vll SMP Negeri 1 Sipoholon Tahun Pembelajaran 2022/2023 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to determine the positive and significant influence of providing learning motivation by Christian Religious Education teachers on the learning outcomes of class VII students at SMP Negeri 1 Sipoholon for the 2022/2023 academic year. The method used in this research is a quantitative research method with a descriptive statistical approach. The population is all class VII students of SMP Negeri 1 Sipoholon for the 2022/2023 academic year, totaling 160 people and a sample of 32 people was determined using the purposive sampling technique. Data was collected using a positive closed questionnaire with 25 items for variable Test analysis requirements: a) a positive relationship test obtained a value of rxy = 0.504 > rtable(=0.05,n=32) = 0.349. b) Testing a significant relationship obtained tcount= 3.198 > ttable(=0.05, dk=n-2=30)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=